2018
DOI: 10.1093/mnrasl/sly080
|View full text |Cite
|
Sign up to set email alerts
|

Mass-invariance of the iron enrichment in the hot haloes of massive ellipticals, groups, and clusters of galaxies

Abstract: X-ray measurements find systematically lower Fe abundances in the X-ray emitting haloes pervading groups (kT 1.7 keV) than in clusters of galaxies. These results have been difficult to reconcile with theoretical predictions. However, models using incomplete atomic data or the assumption of isothermal plasmas may have biased the best fit Fe abundance in groups and giant elliptical galaxies low. In this work, we take advantage of a major update of the atomic code in the spectral fitting package spex to re-evalua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 48 publications
(61 reference statements)
6
38
2
Order By: Relevance
“…15 shows model results for the relation between the temperature of the hot ICM at r 500 , T 500 (a proxy for the gravitating mass), and the mean iron abundance within r 500 (the black points). Also shown are the observational dataset from Yates et al (2017) for clusters (orange points), and from Mernier et al (2018b) for clusters and groups (light blue points).…”
Section: Metal Content In the Icmmentioning
confidence: 99%
See 2 more Smart Citations
“…15 shows model results for the relation between the temperature of the hot ICM at r 500 , T 500 (a proxy for the gravitating mass), and the mean iron abundance within r 500 (the black points). Also shown are the observational dataset from Yates et al (2017) for clusters (orange points), and from Mernier et al (2018b) for clusters and groups (light blue points).…”
Section: Metal Content In the Icmmentioning
confidence: 99%
“…The same procedure is also applied to our model systems, which are assumed to have a Mernier et al (2017) profile when re-scaling the iron abundance from within r 200 to within r 500 (see Section 5 of Yates et al 2017 for details. ) Second, we take account of recent improvements to the way iron abundances are obtained from the X-ray spectra of galaxy groups (Mernier et al 2018b) by excluding from our comparison the observational data for galaxy groups compiled by Yates et al (2017) that relied on Z Fe estimates obtained from older spectral-fitting codes. For clusters, Mernier et al (2018b) found little difference in the Z Fe estimates obtained from older and newer versions of SPEX-ACT.…”
Section: Metal Content In the Icmmentioning
confidence: 99%
See 1 more Smart Citation
“…Another (yet no less important) source of systematic uncertainties concerns our current knowledge of the atomic processes that produce the continuum and the emission lines in ICM spectra. For instance, it has been shown that improvements in atomic codes can significantly affect measurements of absolute Fe abundances in groups and ellipticals (Mernier et al ) and of X/Fe abundance ratios in more massive systems (Mernier et al ), thereby altering their astrophysical interpretations. Nowadays, most of the ICM abundances reported in the literature rely on two sets of atomic codes/tables (Table ).…”
Section: Atomic Codes and Systematic Uncertaintiesmentioning
confidence: 99%
“…Uncertainties regarding the atomic codes are limited by the fact that we are using the update of the code SPEXACT and SPEX, which incorporate more precise modelling of the atomic processes and extensive compilation of transitions. However, uncertainties due to a not complete atomic database are still present (Hitomi Collaboration et al 2018) and their effects can be nonnegligible (Mernier et al 2018a).…”
Section: Systematic Uncertaintiesmentioning
confidence: 99%